Digital Natives Preferences in How to Learn Mathematics: A Qualitative Study of Preservice Mathematics Teachers - Taulia Damayanti; Bertu Rianto Takaendengan; Putri Ekawaty Kobandaha; Wimansya Gombah (Jambura Journal of Mathematics Education, 2023)
The purpose of this study was to describe how digital natives as preservice mathematics teachers learn mathematics. The research subjects were 30 students of the Mathematics Education Study Program at the Universitas Negeri Gorontalo. This research is a descriptive qualitative research with data collection techniques are semistructured interview, questionnaire using Mentimeter, and documentation. Data collecting held in 2022. First, they were interviewed to obtain information on how they studied college mathematics courses such as calculus or differential equations. After obtaining the methods they used, they were then asked to fill out a questionnaire via Mentimeter. From the results of the interviews and filling out the questionare, it was found that their ways of learning were by watching YouTube, reading books, discussing mathematics material with their peers, searching for learning material from the internet, and also using mathematical applications to help them solving problems. Although everyone has different preferences for which method they like the most, in general, they combine all five learning styles. When they were asked to choose the method they liked the most, 50% of them choose watching YouTube; 43% prefer to learn from books; and 6.67% choose to use mathematical application. The mathematical applications they use are dominated by Photomath. Other applications used are Qanda, Brainly, Colearn, Mathway, MathLab, Mathenchanter, Geogebra, Snap Quiz, and Wolfram Alpha. The results show that book is still relevan to use in this digital age.